Public knowledge and practices toward safe disposal of unused and expired medications in Palestine: a cross-sectional study - Anas K. Assi; Alhareth M. Amro; Salahaldeen Deeb; Habeeb H. Awwad; Malak K. Assi; Ahmad K. Assi; Samer Amayra; Ali Nassr; Omar Jehad Arman; Abdalqader Alwohoush; Ahmed Zaid; Mohammad Amouri; et al. (Frontiers in Public Health, 2026)
Background Improper disposal of unused and expired medications poses significant health and environmental risks worldwide, especially in resource-limited and conflict-affected settings where pharmaceutical waste management infrastructure is lacking and antimicrobial resistance (AMR) is rising. Population-level data from fragile healthcare systems in the Middle East are scarce. This study assessed knowledge, attitudes, and practices (KAP) related to medication disposal among Palestinian adults in a setting without formal take-back programs or national disposal guidelines, and analyzed behavioral determinants to inform pragmatic AMR prevention and waste management strategies. Methods A cross-sectional study was conducted using an online survey. A total of 402 non-healthcare Palestinian adults (≥18 years) were recruited via non-probability snowball sampling. A structured questionnaire was administered online. While this approach enabled wide reach; however, it may have limited representativeness of older and less digitally connected individuals. We utilized multivariable logistic regression to identify predictors of behavior based on HBM constructs. To strengthen inferential validity, causal mediation analysis was performed to assess whether perceived barriers mediated the relationship between risk perception and disposal practices. Internal consistency was assessed with Cronbach’s α , and data were analyzed using SPSS v25 with a p < 0.05 considered significant. Results Respondents were predominantly female (67.4%) with mean age 27.2 ± 9.6 years. Specific environmental knowledge was limited: 40.8% knew flushing contaminates groundwater and 29.4% linked improper disposal to antibiotic resistance. Although 93% supported professional guidance and public awareness, unsafe practices predominated: 77.4% discarded expired medications in household garbage and only 9.7% returned them to pharmacies. Multivariable analysis showed perceived risk was the strongest positive predictor of safe disposal, while perceived barriers significantly reduced odds of safe behavior. Mediation analysis found no significant indirect effect of risk via barriers, indicating independent pathways. Weighted sensitivity analyses confirmed the robustness of the risk–behavior association. Conclusion Positive attitudes coexist with inadequate disposal practices in Palestine. Structural barriers, not lack of risk awareness alone, sustain unsafe behaviors. Effective policy must combine risk communication with removal of logistical obstacles—most feasibly through accessible pharmacy-based take-back programs and supportive operational policies—to translate awareness into safer disposal and reduce environmental risks.